Nurse Caring Behavior Analysis In Term Of Performance and Workload Satisfaction Of Lavalette Malang Hospital - Fawzi, Alfian; Saifulah, Dedi; Kusumawati, Prima Dewi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Caring is an art and science approach to caring for clients in the form of a dynamic approach between nurses and patients. The design of this study is descriptive correlational research that examines the influence between variables. The population in this study were patients who were given caring behavior and functional nurses with a simple random sampling method of 36 respondents. The independent variable is job satisfaction and nurse workload while the dependent variable is caring behavior with multiple linear regression statistical tests. The results of the study were nurses caring behavior in Lavalette Malang hospital majority (94 %) as many as 34 respondents were calssified as good. The results of multiple linear regression tests obtained p value: 0,015<α = 0,05. There is an influence of workload and nurse performance satisfaction on caring behavior. The most dominant factor based on the partial T-test analysis of variables is performance satisfaction